Rate determining step in SDC-SSAF dual-phase oxygen permeation membrane - Li, C.; Li, W.; Chew, J.; Liu, Shaomin; Zhu, X.; Sunarso, J. (Elsevier BV, 2019)
Dense mixed ionic-electronic conducting (MIEC) dual-phase Ce0.85Sm0.15O1.925–Sm0.6Sr0.4Al0.3Fe0.7O3-d (SDC-SSAF) represents one of the most attractive oxygen-selective membrane materials for oxygen separation from air above 700 °C. Its high phase stability in reducing atmosphere and CO2 resistance allows its potential direct integration into oxyfuel combustion and membrane reactor applications. In this work, the oxygen permeation parameters and properties of SDC-SSAF are evaluated theoretically using the Zhu model, which analyses the role of interfaces in electrochemical oxygen permeation. The model produced good correlation with the experimental data (R2 = 0.9990), with the calculated resistance constants indicating higher resistance encountered at the feed side interface as compared to the permeate side. An analysis of the characteristic thickness indicates increasing influence of surface exchange reactions with decreasing temperature, feed side pressure, and permeate side pressure. Although oxygen permeation is dependent upon various operating conditions, our parametric study reveals that temperature effect surpasses oxygen partial pressure difference effect in enhancing the oxygen permeation flux. Oxygen permeation is limited by surface reactions between 800 and 850 °C and mixed bulk diffusion and surface exchange reactions between 850 and 875 °C. Above 875 °C, the rate determining step shifts to bulk diffusion.